Let the best story win – evaluation of the most cited business history articles. Issue 4 (2nd October 2017) - Ojala, Jari; Eloranta, Jari; Ojala, Anu; Valtonen, Heli
Abstract: Faced with intensifying competition for scientific impact measured in terms of citation counts, small disciplines are challenged to prove their importance as they lack the critical mass to accumulate large numbers of citations. This paper demonstrates that by emphasizing theoretical and methodological rigor even small disciplines such as business history can be competitive. Yet it still appears that readers of business history articles first and foremost seek interesting and useful subject matter, i.e. 'best' stories that can be used as background information and as tools in comparisons. However, articles advancing theory and methodology have increasingly gained interest and citations from other business historians as well as from scholars in related disciplines. Thus, business history scholarship using a sound theoretical framework to analyze relevant cases score more citations both inside and outside the field, leading to fruitful debates that serve to enhance the discipline.